Shaping the Future - A Difficult Task - Epure, Manuela (Journal of Economic Development, Environment and People, 2015)
Living in today’s world is not easy: as a human being you need to adapt yourself to a hostile environment where unforeseen challenges emerge, keeping us in constant alert. Economic development is directly connected to human development; therefore sustainable economic growth needs to be the central point of the current development strategies, not only at country level but mainly at global scale....